Outcomes of Allogeneic Hematopoietic Cell Transplantation in Patients with Dyskeratosis Congenita - Shahinaz M. Gadalla; Carmem Sales‐Bonfim; Jeanette Carreras; Blanche P. Alter; Joseph H. Antin; Mouhab Ayas; Prasad Bodhi; Jeffrey Davis; Stella M. Davies; Éric Deconinck; H. Joachim Deeg; Reggie Duerst; et al. (2013)
We describe outcomes after allogeneic transplantation in 34 patients with dyskeratosis congenita who underwent transplantation between 1981 and 2009. The median age at transplantation was 13 years (range, 2 to 35). Approximately 50% of transplantations were from related donors. Bone marrow was the predominant source of stem cells (24 of 34). The day-28 probability of neutrophil recovery was 73% and the day-100 platelet recovery was 72%. The day-100 probability of grade II to IV acute GVHD and the 3-year probability of chronic graft-versus-host disease were 24% and 37%, respectively. The 10-year probability of survival was 30%; 14 patients were alive at last follow-up. Ten deaths occurred within 4 months from transplantation because of graft failure (n = 6) or other transplantation-related complications; 9 of these patients had undergone transplantation from mismatched related or from unrelated donors. Another 10 deaths occurred after 4 months; 6 of them occurred more than 5 years after transplantation, and 4 of these were attributed to pulmonary failure. Transplantation regimen intensity and transplantations from mismatched related or unrelated donors were associated with early mortality. Transplantation of grafts from HLA-matched siblings with cyclophosphamide-containing nonradiation regimens was associated with early low toxicity. Late mortality was attributed mainly to pulmonary complications and likely related to the underlying disease.